2022
DOI: 10.1007/s10637-022-01269-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of amrubicin monotherapy after atezolizumab plus carboplatin and etoposide in patients with relapsed small-cell lung cancer

Abstract: This study examined the activity and safety of amrubicin monotherapy among relapsed small-cell lung cancer (SCLC) patients who had previously been treated with atezolizumab plus carboplatin and etoposide (AteCE). This retrospective study evaluated patients with relapsed SCLC who were treated with previously AteCE combination therapy followed by amrubicin monotherapy between August 2019 and May 2021. Clinical efficacy and toxicity were analyzed. Overall, 40 patients were included: 12 and 28 patients had sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Some studies have reported the efficacy and safety of AMR after administration of ICIs in patients with SCLC. These studies also revealed that the incidence of severe toxicities associated with AMR did not increase following treatment with ICIs 6,11,12 . Moreover, a recent study reported the efficacy of combination Pem and AMR therapy as second‐line treatment for SCLC, including median OS of 10.6 months and median PFS of 4.0 months 13 .…”
Section: Discussionmentioning
confidence: 94%
“…Some studies have reported the efficacy and safety of AMR after administration of ICIs in patients with SCLC. These studies also revealed that the incidence of severe toxicities associated with AMR did not increase following treatment with ICIs 6,11,12 . Moreover, a recent study reported the efficacy of combination Pem and AMR therapy as second‐line treatment for SCLC, including median OS of 10.6 months and median PFS of 4.0 months 13 .…”
Section: Discussionmentioning
confidence: 94%
“…Although no phase 3 study previously evaluated the efficacy of amrubicin in combination with platinum doublet and ICI therapy in ED‐SCLC, a study reported a median OS of 11.7 months in sensitive relapse and 7.3 months in refractory relapse after treatment with atezolizumab plus carboplatin and etoposide 13 . These data indicate that amrubicin is an effective and feasible second‐line treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…The IMPOWER133 trial showed that adding ICIs to carboplatin and etoposide improved survival in patients with ES‐SCLC compared to chemotherapy alone 21 . However, other trials failed to show any benefit of ICIs as a second‐line treatment for ES‐SCLC 22–25 . Thus, it seems that the efficacy of ICIs is mainly observed during the first‐line treatment and that subsequent ICI therapy may not be effective for patients who did not respond to first‐line ICI plus chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“… 21 However, other trials failed to show any benefit of ICIs as a second‐line treatment for ES‐SCLC. 22 , 23 , 24 , 25 Thus, it seems that the efficacy of ICIs is mainly observed during the first‐line treatment and that subsequent ICI therapy may not be effective for patients who did not respond to first‐line ICI plus chemotherapy. Therefore, it is crucial to identify biomarkers that can predict the response to first‐line ICI plus chemotherapy and guide the selection of patients who may benefit from this treatment.…”
Section: Discussionmentioning
confidence: 99%